Case Report: Progression of a Silent Corticotroph Tumor to an Aggressive Secreting Corticotroph Tumor, Treated by Temozolomide. Changes in the Clinic, the Pathology, and the β-Catenin and α-SMA Expression - Demarchi, Gianina; Perrone, Sofía; Esper Romero, Gaela; De Bonis, Cristian; Casasco, Juan Pablo; Sevlever, Gustavo; Berner, Silvia Ines; Cristina, Carolina (Frontiers in Endocrinology, 2022)
Clinically silent corticotroph tumors are usually macroadenomas that comprise 20% of ACTH tumors. They frequently progress to aggressive tumors with high recurrence, invasiveness and in rare occasions, they may become hormonally active causing Cushing disease. Trustable biomarkers that can predict their aggressive course as well as their response to traditional or new therapies are paramount. Aberrant β-Catenin expression and localization have been proposed as responsible of several malignancies including pituitary tumors. Nevertheless, the role of β-Catenin in the aggressive transformation of silent corticotropinomas nor in their response to Temozolomide salvage treatment have not been explored yet. In this work, we present a case of a silent corticotroph tumor that invaded cavernous sinus and compressed optic chiasm and, after a first total resection and tumor remission it recurred six years later as an aggressive ACTH-secreting tumor. This lesion grown with carotid compromise and caused Cushing 's signs. It required multiple medical treatments including Cabergoline, Ketoconazole, TMZ and radiotherapy. Besides, other two surgeries were needed until it could be controlled. Interestingly, we found α-SMA vascular area reduction and differential β-Catenin cell localization in the more aggressive tumor stages characterized by high Ki-67 indexes and p53 expression. Our results may indicate a role of angiogenesis and β-Catenin trigged events in the pituitary tumor transformation, which could in turn affect the response to TMZ and/or conventional treatments. These molecular findings in this unusual case could be useful for future management of aggressive pituitary tumors.